Faktor Penyebab Kesulitan Siswa Dalam Pelaksanaan Pembelajaran Daring: Survei di SDN 2 Mapin Kebak - Nopitasari Nopitasari; Nasaruddin Nasaruddin; Heri Setiawan; I Nyoman Karma (Journal of Science Instruction and Technology, 2021)
This study aims to determine the level of factors that cause student difficulties in implementing online learning at SDN 2 Mapin Kebak in the 2020/2021 school year. The subjects in this study were classes II, III, IV and V, totaling 89 students, while the object was the students' difficulties in online learning. The data collection technique uses a questionnaire with a survey method. The data analysis technique used is descriptive quantitative with percentages. The results of the study generally show the level of factors that cause student difficulties in implementing online learning at SDN 2 Mapin Kebak for the 2020/2021 school year in the "Very High" category of 0% (0 students), the "High" category 31.46% (28 students), the "Medium" category was 44.94% (40 students), the "Low" category was 13.48% (12 students), and the "Very Low" category was 10.11% (9 students). The principal can form a quality control team to monitor so that the online learning process can be carried out optimally. Teachers can also be given training related to the use of information technology in online learning. Furthermore, socialization to parents of students about their roles and responsibilities during the implementation of online learning. This is done to reduce the level of difficulty of the students, whether it is caused by factors from teachers, technology, and students themselves.